Aryl hydrocarbon receptor nuclear translocator-like (BMAL1) is associated with susceptibility to hypertension and type 2 diabetes. - Woon, P; Kaisaki, P; Bragança, J; Bihoreau, M; Levy, J; Farrall, M; Gauguier, D (2007)
Many aspects of physiology and behavior follow a circadian rhythm. Brain and muscle Arnt-like protein-1 (BMAL1) is a key component of the mammalian molecular clock, which controls circadian oscillations. In the rat, the gene encoding Bmal1 is located within hypertension susceptibility loci. We analyzed the SNP distribution pattern in a congenic interval associated with hypertension in the spontaneously hypertensive rat (SHR), and we show that Bmal1 maps close to a region genetically divergent between SHR and its normotensive (Wistar-Kyoto) counterpart. Bmal1 sequencing in rat strains identified 19 polymorphisms, including an SHR promoter variant that significantly affects Gata-4 activation of transcription in transient transfection experiments. A genetic association study designed to test the relevance of these findings in 1,304 individuals from 424 families primarily selected for type 2 diabetes showed that two BMAL1 haplotypes are associated with type 2 diabetes and hypertension. This comparative genetics finding translated from mouse and rat models to human provides evidence of a causative role of Bmal1 variants in pathological components of the metabolic syndrome.